Traditional Sport Model to Improve Fundamental Movement Skills and Social Attitudes of Students During COVID-19 - Mujriah Mujriah; Siswantoyo Siswantoyo; Pamuji Sukoco; Friska Octavia Rosa; Ermawan Susanto; Edi Setiawan (OVS LLC, 2022)
The study purpose. COVID-19 caused many negative impacts, including a significant decrease in the fundamental movement skills and social attitudes among students, which becomes the main problem in this study. Therefore, this study aims to investigate the effect of traditional sport on improving students' fundamental movement skills and social attitudes. Materials and methods. This study adopted an experimental method with a pretest-posttest design. The subjects were elementary school students in Yogyakarta city and they were selected using random sampling (n = 30). The traditional sports program was carried out for 7 weeks with once-a-week meetings. The instrument for assessing students' fundamental movement skills was using a gross motor development test and social attitudes were assessed using the questionnaire of Physical Education Activity Attitude. Shapiro-Wilk was used to test the normality of the data, while the Paired Sample t-test was used to assess differences in the values of students' fundamental movement skills and social attitudes before and after the program. Results. The results of this study indicate that traditional sports have a significant effect on improving fundamental movement skills (p < 0.05) and social attitudes (p < 0.05). Conclusions. Thus, traditional sports programs can be used as an alternative activity that can be used by physical education teachers during the COVID-19 crisis.